2021
DOI: 10.1177/17411432211041625
|View full text |Cite|
|
Sign up to set email alerts
|

Leadership styles and teacher job satisfaction in Ethiopian schools

Abstract: This quantitative study investigated the relationship between leadership styles and teacher job satisfaction in Ethiopia, based on teacher perceptions. The multifactor leadership theory also known as full range leadership theory and work adjustment theory provided the theoretical framework to explore the relationship. Analysis of data yielded three major findings: (1) while the practice of transformational leadership was significantly lower, the practice of laissez-faire was significantly higher than internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This evidence shows that in view of the domain of the SIP, principals are expected to obtain solid IL skills to enhance teaching and learning and acquire strategic TL that aims to foster the community involvement that the SIP seeks (Abdi, 2016;Kene et al, 2021;Meresa et al, 2019;Solomon, 2016). On the other hand, the latest evidence demonstrated that principals practice TL more than IL and other leadership behaviors (e.g., Kene et al, 2021;Yohannes & Wasonga, 2021); the study illustrates that no significant improvement in student academic achievement was observed throughout the years (Kene et al, 2021). Although school principals are exhaustively engaged in political activities that disregard instructional and curriculum practice by involving teachers, staff members, and community members of the school (Dabesa & Cheramlak, 2021;Ebuy, 2010;Haile, 2020;Meresa et al, 2019), they are also involved in repetitive political meetings and paperwork (Alemayehu, 2021;Edamo & Netshitangani, 2018;Elias, 2020;Geleta, 2017;Haile & Smit, 2021;Mitchell, 2015;Tsegaye, 2018).…”
Section: School Leadership Practice In Ethiopiamentioning
confidence: 99%
See 3 more Smart Citations
“…This evidence shows that in view of the domain of the SIP, principals are expected to obtain solid IL skills to enhance teaching and learning and acquire strategic TL that aims to foster the community involvement that the SIP seeks (Abdi, 2016;Kene et al, 2021;Meresa et al, 2019;Solomon, 2016). On the other hand, the latest evidence demonstrated that principals practice TL more than IL and other leadership behaviors (e.g., Kene et al, 2021;Yohannes & Wasonga, 2021); the study illustrates that no significant improvement in student academic achievement was observed throughout the years (Kene et al, 2021). Although school principals are exhaustively engaged in political activities that disregard instructional and curriculum practice by involving teachers, staff members, and community members of the school (Dabesa & Cheramlak, 2021;Ebuy, 2010;Haile, 2020;Meresa et al, 2019), they are also involved in repetitive political meetings and paperwork (Alemayehu, 2021;Edamo & Netshitangani, 2018;Elias, 2020;Geleta, 2017;Haile & Smit, 2021;Mitchell, 2015;Tsegaye, 2018).…”
Section: School Leadership Practice In Ethiopiamentioning
confidence: 99%
“…Ethiopia has exhibited a radical 500% improvement in basic or primary education enrollment (MoFED, 2012 Gurmu, 2020; Mitchell, 2015), despite the poor school infrastructure, instructional practice, school leadership, and underdeveloped education system (Yohannes & Wasonga, 2021). Hence, school principals in primary and secondary schools in Ethiopia officially obtained autonomy (decentralized system) in administering and decision‐making regarding financial, human, and physical resources through a feasible national package known as the General Education Quality Improvement Package (GEQIP) in 2007, which consisted of six sets of programs, namely, the School Improvement Program (SIP), Information Communication Technology (ICT), Civic and Ethical Education Program, Teacher Development Program (TDP), Curriculum Improvement Program, and School Management and School Leadership (Abdi, 2016; Ebuy, 2010; Edamo & Netshitangani, 2018; Gedifew, 2020; Gurmu, 2018; MOE, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the well-documented impact of national policy on instructional leadership, a growing literature highlights the role that the national policy system plays in fostering transformational leadership in China’s schools (Dou et al, 2016; Sun et al, 2018). Within the top-down national policy process, the top/central policy makers demand the subordinate/local officials to attempt new ways to solve educational problems and expediate school innovation and then back into the formulation of national policy from down-to top (Heilmann, 2008; Lee & Chiu, 2017; Yohannes & Wasonga, 2021).…”
Section: Principal Leadership Style and Students’ Achievementmentioning
confidence: 99%